A visually-oriented quality improvement data management system. (11th May 2004) - Bala, Dinesh; Batson, Robert G.; Moynihan, Gary P.; Ray, Paul S.
This article is a case study of how an automobile door manufacturer developed and uses a Quality Improvement Data Management System based on existing in-process inspection records, specifically those for metal surface defects on the outer door. The authors explain their belief that automotive suppliers who do not capitalise on the potential value of their quality records to steer quality improvement are missing out on a ready source of competitive advantage. The main features of the system are its ability to stratify the inspection data into numerous dimensions, focus on visual presentation of the information, integration of simple statistical tools, such as defect concentration diagrams, and ease of use. These features were desired by potential users including the quality manager, quality engineers, and quality improvement teams, and guided the system design. The system design and software implementation are described, and example applications to real production records are provided.